2020
DOI: 10.4143/crt.2019.328
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Lymph Node Metastasis as a Prognostic Significance in Cervical Cancer: Comparison between Disease Status

Abstract: PurposeLymph node metastasis (LNM) is the most significant prognostic factor in cervical cancer that was recently incorporated into the International Federation of Gynecology and Obstetrics (FIGO) staging system. This study was performed to evaluate whether the prognostic significance of LNM differs according to disease status.Materials and MethodsPatients with FIGO stage IB or higher cervical cancer who had pretreatment computed tomography and/or magnetic resonance imaging studies as well as long-term follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…In the present study, large tumor size was associated with histopathologically verified parametrial infiltration and lymph node metastasis in surgically treated patients, as well as with positive corresponding MRI findings guiding stage assignment in 2018 FIGO staging system [ 2 ]. This is in line with prior studies reporting associations between large tumor size (both histopathological and MRI-measured) and pathologically enlarged lymph nodes on MRI [ 31 ], as well as with histologically verified lymph node metastases or parametrial infiltration [ 11 – 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, large tumor size was associated with histopathologically verified parametrial infiltration and lymph node metastasis in surgically treated patients, as well as with positive corresponding MRI findings guiding stage assignment in 2018 FIGO staging system [ 2 ]. This is in line with prior studies reporting associations between large tumor size (both histopathological and MRI-measured) and pathologically enlarged lymph nodes on MRI [ 31 ], as well as with histologically verified lymph node metastases or parametrial infiltration [ 11 – 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…CC is a common gynaecologic malignant tumour for which postoperative recurrence and metastasis are the main causes of death ( 15 , 16 ). Patients with early-stage CC always have a better prognosis after surgery ( 2 ) but worse prognosis when proven to be metastatic.…”
Section: Discussionmentioning
confidence: 99%
“…Although all studies developed a prediction tool for CC prognosis based on completely different genes, our research paid more attention to the integration of the four-gene prognostic signature and lymph node status. The recent change to FIGO staging of CC cases reflects the importance of LNM status, and several reports have demonstrated that positive pathologic LNM is more strongly associated with the survival rate than other risk factors such as age, histology, and clinical stage [ 16 , 17 ], although LNM status alone may not predict CC prognosis. In the present study, we demonstrated that both the four-gene signature and LNM status had prognostic value for CC, and we developed a nomogram that integrated the four-gene prognostic signature and LNM status to accurately predict the 1- and 3-year OS rates of patients with CC.…”
Section: Discussionmentioning
confidence: 99%